Modeling and Analysis of A Prey-Predator-Scavenger System Encompassing Fear, Hunting Cooperation, and Harvesting - Ibrahim, Lubna Riyadh; Bahlool, Dahlia Khaled (Iraqi Journal of Science, 2025)
In this research, a model was taken to explore the relationship between the prey, the predator, and the scavenger in the diet to study dynamic behavior. This was done by forming a system of ordinary differential equations, and critical points were found for the model that match biologically and mathematically to our study. Their existence was proven, and theories were created for the model. By applying local and global stability methods, also we were able determine the bifurcation occurring at particular sites. After that, we observed the result of cooperation in hunting, which greatly affects both prey and predators, playing a vital and influential role. Everything we mentioned above was also proven practically, using Mathematica 13.2 to prove the validity of what we mentioned practically.